Effect of whitening toothpaste on titanium and titanium alloy surfaces - Adriana Cláudia Lapria Faria; Angelo Rafael de Vito Bordin; Vinícius Pedrazzi; Renata Cristina Silveira Rodrigues; Ricardo Faria Ribeiro (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Dental implants have increased the use of titanium and titanium alloys in prosthetic applications. Whitening toothpastes with peroxides are available for patients with high aesthetic requirements, but the effect of whitening toothpastes on titanium surfaces is not yet known, although titanium is prone to fluoride ion attack. Thus, the aim of the present study was to compare Ti-5Ta alloy to cp Ti after toothbrushing with whitening and conventional toothpastes. Ti-5Ta (%wt) alloy was melted in an arc melting furnace and compared with cp Ti. Disks and toothbrush heads were embedded in PVC rings to be mounted onto a toothbrushing test apparatus. A total of 260,000 cycles were carried out at 250 cycles/minute under a load of 5 N on samples immersed in toothpaste slurries. Surface roughness and Vickers microhardness were evaluated before and after toothbrushing. One sample of each material/toothpaste was analyzed by Scanning Electron Microscopy (SEM) and compared with a sample that had not been submitted to toothbrushing. Surface roughness increased significantly after toothbrushing, but no differences were noted after toothbrushing with different toothpastes. Toothbrushing did not significantly affect sample microhardness. The results suggest that toothpastes that contain and those that do not contain peroxides in their composition have different effects on cp Ti and Ti-5Ta surfaces. Although no significant difference was noted in the microhardness and roughness of the surfaces brushed with different toothpastes, both toothpastes increased roughness after toothbrushing.